Making Every Contact Count: health professionals’ experiences of integrating conversations about Snacktivity to promote physical activity within routine consultations – a qualitative study - Kate Jolly; Nanette Mutrie; Thomas Yates; Sheila Greenfield; Ralph Maddison; Emma Frew; Colin Greaves; Magdalena Skrybant; Kajal Gokal; Amanda J Daley; Dale W Esliger; Lauren B Sherar; et al. (BMJ Open)
Objective Helping people to change their health behaviours is becoming a greater feature within the role of health professionals, including through whole system initiatives such as Making Every Contact Count. Health services provide an ideal setting to routinely promote health behaviours, including physical activity. Snacktivity is a novel approach that promotes small bouts of physical activity (activity snacks) throughout the day. This study explored health professionals’ initial experiences of delivering a Snacktivity intervention to promote physical activity within routine health consultations. A further aim was to investigate health professionals’ ability/fidelity in delivering the Snacktivity intervention to their patients.Design Semistructured interviews (n=11) and audio recording of consultations (n=46).Setting and participants Healthcare professionals from a variety of specialisms who delivered the Snacktivity intervention within patient consultations.Results Analyses revealed two higher-level themes of interest: (1) health professionals’ conceptualisation of Snacktivity (subthemes: observations/reflections about patients’ understanding, engagement and enthusiasm for delivering the Snacktivity intervention) and (2) health professionals’ understanding of Snacktivity and experience in delivering the intervention (subthemes: delivering Snacktivity; limitations, challenges and possible improvements). Consultation audio recordings demonstrated health professionals delivered the Snacktivity intervention with high levels of fidelity. Health professionals were proficient and supportive of delivering the Snacktivity intervention within consultations although practical barriers to implementation such as time constraints were raised, and confidence in doing so was mixed.Conclusions Health professionals were proficient and supportive of delivering the Snacktivity intervention within consultations. The primary barrier to implementation was the time to deliver it, however, gaining greater experience in the intervention and improving behaviour change counselling skills may reduce this barrier.Trial registration number ISRCTN64851242.